Investigations of Changes of Stinging Nettle’s (Urtica dioica L.) Crop Density (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Recently all countries are looking for the renewable resources. Stinging nettle (Urtica dioica L.) is a perennial plant owning many valuable properties, including yielding natural fibres. Fiber nettle is a cultivated form of the wild nettle. The aim of the research was to investigate changes of productivity of stinging nettle’s crop established at different crop densities. Main criterion discussed in the article is the number of the stems per measuring unit (i.e., crop density). The investigation was carried out at the Upytė Research Station of LRCAF in 2008-2012. The crop of different implantation density was established: 60x60 and 60x100 cm. The results of our investigation show that in the first cropping year stinging nettle produced 25-43 stems per plant. Plants from the crop of 2nd year, 60x60, were grosser, more productive than that of the 1st year crop. Plants of the 1st year crop, 60x100, had more stems per plant than that of 1st year crop, 60x60, but amount of stems per ha1 was higher in the crop of 1st year crop, 60x60. The inundation early in 2010 led to the decrease of plant density of stinging nettle’s crop. Crop density in the spring was lower than that in the autumn. The greatest increase of amount of stems per plant was found in the plots of lower implantation density (60 x 100 cm). It could be that the optimal crop density (112-136 plants m-2) was already achieved in the crop of 4th and 5th cropping year, and it will not increase any more in more matured crop in following years. Further investigation would be intrigued.